Pemanfaatan Kulit Garcinia mangostana L. sebagai Imunomodulator untuk Meningkatkan Kualitas Sumber Daya Manusia: Sebuah Tinjauan Sistematis: Utilization of Garcinia mangostana L. Peel as an Immunomodulator to Improve the Quality of Human Resources: A Systematic Review - Pratiwi, Yunita Satya; Rini, Dina Mustika; Defri, Ifwarisan; Qubra, Tawaffani; Maulidi, Nadien Mutia Intan (Amerta Nutrition, 2025)
Background: Mangosteen (Garcinia mangostana L.) is recognized for its immunomodulatory properties, which can rejuvenate, regulate, and modulate immune system function. As a rich source of antioxidants, mangosteen peel has the potential to enhance immune responses and improve overall health status. However, further investigation into the biological mechanisms underlying its immunomodulatory effects remains limited. Objectives: This review aims to explore the various biological functions of mangosteen peel related to immunomodulation and examine its therapeutic potential in improving human health. Methods: A Systematic Literature Review (SLR) was conducted, focusing on articles published between 2013 and 2023. From a total of 132 articles identified, ten were selected based on relevance and research quality. Discussions: The review reveals significant associations between the properties of mangosteen peel, such as its anti-diabetic, anti-obesity, antidepressant, anti-inflammatory, anticancer, and antioxidant activities, and the complex network of immune cell responses. Nevertheless, most studies have not clearly identified the specific compounds responsible for these immunomodulatory effects, and the underlying mechanisms remain unclear. Further comprehensive studies are necessary to isolate and identify the bioactive compounds in mangosteen peel extract, beyond xanthones, to better understand their diverse therapeutic effects and mechanisms. Well-designed clinical trials involving diverse populations, including vulnerable groups, are essential to validate the efficacy and safety of the extract in various therapeutic contexts. Conclusions: This review provides valuable insights into the potential of mangosteen peel as an immunomodulator and lays the groundwork for future research aimed at utilizing its therapeutic properties to improve human health.